Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen dan Implikasinya Terhadap Niat Berperilaku Konsumen Toko Buku - Yohanes .; YB. Andre Marvianta (Ilmiah Manajemen Bisnis, 2014)
ABSTRACTThe purpose of this study was to determine the relationship of service quality to customer satisfaction, customer satisfaction to behavioural intention and service quality to behavioural intentions for customer. Sample used in this research is 150 respondents, which respondents is university student that have been used products and services from a bookstore. The data has analyzed with Structural Equation Modelling (SEM). It has been discovered that there is only two out of three hypotheses are accepted. Here are the result of those three hypotheses: 1.Service Quality has significant to Customer Satisfaction, 2.Customer Satisfaction has significant to Behavioural Intentions. 3.Service Quality has not significant to Behavioural Intentions.Keywords: Service Quality, Customer Satisfaction, Behavioural Intentions